EMOTIONAL ATTRACTION IN ELECTION CAMPAIGN ADVERTISING - Saeed , Payman (Humanities Journal of University of Zakho, 2025)
Emotion is a state of feeling versus perception that arises from all five senses. Emotion and reason are two basic pillars of human thought that have an influential role in behavior. Emotion is more effective and takes less time to persuade and change direction and attitudes, so it is used as an important factor in election campaign advertisements. Election advertising has great importance in politics, especially during elections, where parties and candidates try to influence the public and win their votes by advertising themselves through mass communication channels. Such as television, radio, internet, newspapers, magazines, posters, etc. In the context of the sixth round of the Kurdistan Regional Government parliamentary elections, emotional appeal was strategically employed in candidates’ and party lists’ advertisements to garner public support. The primary objective of electoral advertising is to align with public interests, with the overarching aim of influencing voter behavior and encouraging participation in the electoral process.